SIKLUS BELAJAR MAHASISWA PROGRAM STUDI TADRIS KIMIA FAKULTAS TARBIYAH DAN KEGURUAN UIN ANTASARI BANJARMASIN DI TENGAH PANDEMI COVID-19 - Ardian Trio Wicaksono (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2022)
The Covid-19 pandemic has resulted in learning that was originally direct to be indirect. This condition resulted in a change in the learning cycle from offline to online. The learning cycle discussed consists of: exploring, introducing and applying concepts. This study is to determine the implementation of the student learning cycle of the Tadris Chemistry Study Program, Faculty of Tarbiyah and Teacher Training at UIN Antasari Banjarmasin in the midst of the Covid-19 pandemic and the factors that influence it. This type of research is a field research using a qualitative approach. Data collection techniques using online interviews through google meet. The results showed that the learning cycle in the form of exploring, introducing and applying concepts had not been fully implemented and there were factors that influenced it in the form of many tasks, decreased body immunity, colliding learning time, laziness, network constraints, Korean dramas, delaying assignments, completing homework, lack of motivation and reference as well as viewing social media such as youtube.